Study on the effects of Bt gene on agronomic traits of rice using near isogenic lines - SHEN Sheng-quan; SHU Qing-yao; BAO Jin-song; WU Dian-xing; XIA Ying-wu (浙江大学学报. 农业与生命科学版)
With Milyang 46 (MY46) taken as recurrent line and a transgenic Bt rice (KMD1) as donor line, an isogenic line with Bt gene (RIMY46) was constructed by consecutive backcrosses and selections with GUS reaction as a marker. It was found that GUS reaction and PCR amplification test for Bt gene were positive with all RIMY46 and II32A/RIMY46 hybrid plants, and all lines were highly resistant to lepidopteran insects. In early vegetative stage, the plant height and tiller number were lower for RIMY46 than those for MY46. However, in all late stages, eight agronomic traits and nine quality traits were almost identical except for late heading date and lower head milled rice percentage in RIMY46. The crosses of II32A/RIMY46 and II32A/MY46 showed no difference in all traits investigated, indicating that Bt gene had no negative effects on the hybrid rice.